Thinking English translation analysing and translating English source texts - Cragie, Stella; Pattison, Ann (London Routledge/Taylor & Francis Group, 2018)
"Thinking English Translation is a practical guide to analysing and translating English source texts. Section I focuses on pre-translation analysis where students are guided to consider the features of a variety of English texts and the various implications for translation into other languages. Section II examines language variety in English in more detail and provides strategies for dealing with translation challenges in a wide range of text types. Thinking English Translation gives students a framework for a better understanding of how to approach source texts in order to tackle translation assignments, whether in class or in the workplace, with confidence"--Provided by publisher.
Introduction -- SECTION 1: Pre-translation analysis - Criteria and features -- 1.1 Levels of reading -- 1.2 Pre-translation analysis criteria -- 1.3 Pre-translation analysis table - Stage one -- SECTION 2: English as a source language -- 2.1 Language variety and quality -- 2.2 Culture and context -- 2.3 Translation strategies -- SECTION 3: Sample analyses -- 3.1 Pre-translation analysis table - Stage two -- 3.2 Samples of full analysis -- 3.3 Fast-track analyses -- SECTION 4: Sample translations -- Conclusion.
Includes bibliographical references (pages 125-128) and index.
Keywords: Language and languages -- Transliterations in English; English language -- Variations -- Foreign countries